2016
DOI: 10.1016/j.jtcme.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coleus forskohlii and its major constituents on cytochrome P450 induction

Abstract: Coleus forskohlii Briq. has been used traditionally for the treatment of several ailments since antiquity in Ayurveda. In the present study, an approach has been made to evaluate the effect of C. forskohlii and its major constituents on cytochrome P450 (CYP3A, CYP2B, and CYP2C) mRNA expression in rat hepatocytes. To gain better understanding of the herb–drug interaction potential of the chemical constituents present in C. forskohlii, the extract was subjected to column chromatography followed by standardizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Dig and Staudinger 23 reported that 10 to 100 μM of forskolin concentrations induced CYP3A gene expression through the pregnane X receptor in cultured rodent hepatocytes. In contrast, Hebbani et al 24 reported that forskolin, 1-deoxyforskolin, and 1,9-dideoxyforskolin did not induce any significant mRNA expression of CYP3A, CYP2B, and CYP2C in rat hepatocytes. In the present study, CYP-inducing activity was assessed in vivo in mice because in vitro assay systems are incapable of evaluating the effects of absorption, metabolism, physio- Male C57BL/6 mice were fed diets containing 0.5 w/w of fractionated Fr.1 to 5 or unfractionated W CFE for one week.…”
Section: Discussionmentioning
confidence: 87%
“…Dig and Staudinger 23 reported that 10 to 100 μM of forskolin concentrations induced CYP3A gene expression through the pregnane X receptor in cultured rodent hepatocytes. In contrast, Hebbani et al 24 reported that forskolin, 1-deoxyforskolin, and 1,9-dideoxyforskolin did not induce any significant mRNA expression of CYP3A, CYP2B, and CYP2C in rat hepatocytes. In the present study, CYP-inducing activity was assessed in vivo in mice because in vitro assay systems are incapable of evaluating the effects of absorption, metabolism, physio- Male C57BL/6 mice were fed diets containing 0.5 w/w of fractionated Fr.1 to 5 or unfractionated W CFE for one week.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that mouse Cyp3a11 is a PXR-regulated gene, 36) and CFE induction of CYP has been shown to involve PXR. 23) Differences in the CFE dose required for CYP induction between the intestine and liver may be due to differences in transcriptional regulation of the CYP gene. In an in vivo mouse study, we showed that hepatic CYP induction was promoted by CFE administration, but not by pure forskolin.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have reported conflicting results on CYP induction by CFE. 23,24) In an in vivo mouse study, we reported that CFE induced hepatic hypertrophy and CYP induction at a dose commonly taken as a dietary supplement. 25) In addition, we have shown that CFE interacts with warfarin and tolbutamide via induction of hepatic CYP, resulting in decreased drug ef-ficacy in mouse in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since it inhibits platelet aggregation and clotting, the effect of anti-clotting drugs like warfarin, aspirin, anoxaparin, may be enhanced by the forskolin. Moreover, it has been described that forskolin can induce the expression of cytochrome P450 3A (CYP3A) and can potentially increase the metabolism of drugs that are substrates of related microsomal enzymes (Ding and Staudinger, 2005;Dowless et al, 2005;Virgona et al, 2012;Hebbani Nagarajappa et al, 2015) .…”
Section: Forskolin As An Old Natural Occurring Camp Elevating Compounmentioning
confidence: 99%
“…Interestingly, forskolin is one of the commercially important herbal ingredients for weight loss dietary supplements in the global market (Wagh et al, 2009;Kavitha et al, 2010;Kanne et al, 2015). Its favorable effects on body fat management have been clearly reported (Litosch et al, 1982;Haye et al, 1985;Burns et al, 1987;Shivaprasad et al, 2014) and clinical studies with oral administration of forskolin for up to 50 mg/day as a weight loss agent have not shown relevant side effects in patients (Godard et al, 2005;Henderson et al, 2005;Wagh et al, 2009Wagh et al, , 2012Kavitha et al, 2010;Sharma and Vasundhara, 2011;Hebbani Nagarajappa et al, 2015;Loftus et al, 2015).…”
Section: Forskolin As An Old Natural Occurring Camp Elevating Compounmentioning
confidence: 99%